Recent progress in targeted therapy for non-small cell lung cancer - Xiao, Yanxia; Liu, Pu; Wei, Jie; Zhang, Xin; Guo, Jun; Lin, Yajun (Frontiers in Pharmacology, 2023)
The high morbidity and mortality of non-small cell lung cancer (NSCLC) have always been major threats to people's health. With the identification of carcinogenic drivers in non-small cell lung cancer and the clinical application of targeted drugs, the prognosis of non-small cell lung cancer patients has greatly improved. However, in a large number of non-small cell lung cancer patients, the carcinogenic driver is unknown. Identifying genetic alterations is critical for effective individualized therapy in NSCLC. Moreover, targeted drugs are difficult to apply in the clinic. Cancer drug resistance is an unavoidable obstacle limiting the efficacy and application of targeted drugs. This review describes the mechanisms of targeted-drug resistance and newly identified non-small cell lung cancer targets (e.g., KRAS G12C, NGRs, DDRs, CLIP1-LTK, PELP1, STK11/LKB1, NFE2L2/KEAP1, RICTOR, PTEN, RASGRF1, LINE-1, and SphK1). Research into these mechanisms and targets will drive individualized treatment of non-small cell lung cancer to generate better outcomes.